2021
DOI: 10.5588/pha.21.0038
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance in neonates with suspected sepsis

Abstract: SETTING: Nobel Medical College and Teaching Hospital, Biratnagar, Nepal.OBJECTIVE: To determine the pattern of antimicrobial resistance and hospital exit outcomes in neonates with suspected sepsis in a tertiary neonatal intensive care unit (NICU).DESIGN: This hospital-based cohort study was conducted to follow patients from January to December 2019. All identified cases of suspected sepsis were enlisted from hospital records.RESULTS: Sepsis was suspected in 177 (88%) of the 200 cases admitted in the NICU; 52 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
4
1
0
Order By: Relevance
“…In our study, clinical sepsis was confirmed in 25% of cases with isolation of organisms in blood culture which is similar to other studies [ 10 - 12 ]. As the majority of referral centers do not have facilities for blood cultures, the start of empirical treatment before taking a blood culture in more than 50% of cases may be the reason for sterile culture in most of the cases.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, clinical sepsis was confirmed in 25% of cases with isolation of organisms in blood culture which is similar to other studies [ 10 - 12 ]. As the majority of referral centers do not have facilities for blood cultures, the start of empirical treatment before taking a blood culture in more than 50% of cases may be the reason for sterile culture in most of the cases.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding is similar to a study performed in Nepal where the median TAT was approximately six days [ 25 ], and where, in around two-thirds of the neonates, the antibiotic was changed based on the culture report. In our study due to a large number of neonates being discharged within three days (we speculate that this was due to an improvement in the clinical condition of the neonate), the culture report was not received before discharge for every second neonate.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, clinical sepsis was confirmed (29%) more frequently than in previous reports from Ghana (17% and 22%) [ 5 , 16 ], Saudi Arabia (16%) [ 26 ], but was similar to Nepal (29%) [ 25 ] and lower than in Myanmar (42%) [ 27 ]. Additionally, our proportion of reported culture-confirmed neonates was higher than reported from high-income countries [ 28 ].…”
Section: Discussionsupporting
confidence: 60%
“…Furthermore, the predominance of Gram-positive bacterial isolates identified is consistent with the observation by Sands et al (2022) that they represent the most frequently reported cause of bacterial neonatal sepsis in low-and lower-middle-income countries [17,18]. Similarly, in a previous study in Ghana, CoNS were the most frequently isolated pathogens in early and late-onset infections [11].…”
Section: Discussionsupporting
confidence: 88%
“…SIRS is defined objectively if any two of the four criteria listed here are present: (a) body temperature over 38 or under 36 degrees Celsius; (b) heart rate less than 100 beats/minute; (c) respiratory rate greater than 60 cycles per minute or partial pressure of carbon dioxide less than 32 mmHg; and (d) leucocyte count greater than 12,000/microliters or less than 4000/microliters or there are over 10% immature forms or bands [15,16]. Neonatal sepsis is classified by time of occurrence of infection as early onset sepsis (EOS) in the first 72 h of life and thereafter as late onset sepsis (LOS) [17]. Those who meet the criteria for sepsis are offered empirical treatment in accordance with the STGs for 5-7 days with ampicillin plus gentamicin or ampicillin plus cefotaxime (neonatal sepsis other than cord sepsis), cloxacillin plus gentamicin (neonatal cord sepsis) and ampicillin plus gentamicin plus metronidazole (neonatal bowel related sepsis) [16].…”
Section: Management Of Sepsis In the Study Settingmentioning
confidence: 99%